Legal Nature of the recusal system in Iraqi legislation - Muntadher Sabeeh Dawood ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The responsibility of the judges lies in applying the legal texts with fairness and equality between their litigants and objectively away from accidental influences and without prejudging the cases presented to them before ensuring the availability of evidence and ensuring that there is no suspicion of one of the opponents from the judge’s favoritism to the other party for any reason. As a precautionary measure, the judge must first withdraw from the consideration of any case that may raise doubts on the counterpart of his unfairness, especially if the judgment is not in his favour, and thus the negative impact on the prestige of the judiciary and the loss of confidence of citizens and institutions in the justice of judgments